Salivary diagnostic markers in males and females during rest and exercise - Kay Rutherfurd-Markwick; Carlene Starck; Deborah K. Dulson; Ajmol Ali (Taylor & Francis Group, 2017)
Background Saliva is a useful diagnostic tool for analysis in sports, exercise and nutrition research, as collection is easy and non-invasive and it contains a large number of analytes affected by a range of physiological and pathological stressors and conditions. This study examined key salivary electrolytes and stress and immune markers in males and females at rest and during exercise. Methods Unstimulated whole saliva from 20 healthy, recreationally active participants (8 males and 12 females) was analysed for flow rate, osmolality, sodium (Na+), potassium (K+), chloride (Cl−), secretory immunoglobulin A (SIgA), α-amylase activity and cortisol during both rest and moderate intensity (70% peak power) cycling exercise in a randomised crossover design. Each trial lasted 60 min and sampling was carried out at 15 and 45 min after the start of the trial. Saliva was collected using the gold-standard drool method; participants were required to provide at least 1 mL sample over 2 or 3-min period. Results Females showed a greater response to steady-state exercise stress than males, with significant increases in osmolality (P < 0.001), α-amylase activity (P = 0.001) and secretion rate (P = 0.023) and SIgA secretion rate (P = 0.023), with trends for an increase in K+ (P = 0.053) and decrease in Cl− (P = 0.067). There were no differences between rest and exercise for any salivary analytes in males. In addition, females showed a trend for higher levels of cortisol than males at both rest (P = 0.099) and exercise (P = 0.070), as well as a higher heart rate (P < 0.001) and greater ratings of perceived exertion (P < 0.001) during the exercise trial. The coordination of the two stress response pathways (α-amylase vs cortisol) was positive in males (r = 0.799; P = 0.017) yet negative in females (r = −0.475; P = 0.036). Conclusions Males and females show a markedly different response to steady-state exercise stress as measured in unstimulated whole saliva.